2022
DOI: 10.3390/ijerph19127520
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention and Its Predictors toward COVID-19 Booster Vaccination among Chinese Parents: Applying Two Behavioral Theories

Abstract: The booster vaccination of COVID-19 is being implemented in most parts of the world. This study used behavioral psychology to investigate the predictors of parents’ intentions regarding the COVID-19 booster vaccination for their children. This is a cross-sectional study with a self-designed questionnaire based on two behavioral theories—protective motivation theory (PMT) and theory of planned behavior (TPB). A stratified multi-stage sampling procedure was conducted in Nanjing, China, and multivariable regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
4
6
0
Order By: Relevance
“…Similarly, Li et al [19] showed that attitudes and subjective norms had significant effect on vaccination intentions, with an explanatory power of 73.9%. The findings of Zhou et al [26] are also partially consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Li et al [19] showed that attitudes and subjective norms had significant effect on vaccination intentions, with an explanatory power of 73.9%. The findings of Zhou et al [26] are also partially consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, perceived behavioral control had the strongest influence on parental vaccination intention. A study by Zhou et al [26] also reported that perceived behavioral control, rather than attitudes, had a higher effect on parents' intention to vaccinate their children. However, the study partic-ipants scored below the midpoint (3.19 out of 7 points) on perceived behavioral control, which indicates the perceived ease or difficulty of vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, with regard to TPB-related variables, the results confirmed that attitudes, subjective norms and perceived behavioral control are all internal influencing factors with regard to the willingness to use WHDs. Perceived behavioral control was the most important determinant of willingness, and this is similar to the findings of some other behavioral intention studies, such as in the prediction of intention to screen for cervical cancer in women [ 49 ] and in the research on parental intention to vaccinate their children with the COVID-19 booster vaccine [ 50 ]. Furthermore, perceived behavioral control has also been proved to be the major determinant in several studies on m-Health use [ 44 , 45 , 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…The main drivers for CBVH were fear about the side effects of booster vaccines [ 4 , 21 , 30 , 45 , 47 , 50 ], the severity of side effects associated with previous COVID-19 vaccines [ 26 , 29 , 31 , 34 ], concerns about adverse reactions to booster vaccines [ 6 , 52 ], adverse reactions experienced personally or among friends and family following previous COVID-19 vaccinations [ 5 , 7 , 30 , 52 ], and receipt of medical care following the COVID-19 vaccine primary doses [ 37 ]. Other studies reported uncertainty, risk, and safety concerns associated with booster doses [ 5 , 13 , 20 , 26 , 43 , 44 , 49 , 53 ].…”
Section: Resultsmentioning
confidence: 99%